(untitled) (Proceedings of International Educators Conference, 2024)
The literature review is devoted to the etiology, epidemiology and modern possibilities of treatment of onychomycosis. Information on the use of external and systemic products, as well as new techniques – laser and photodynamic therapy –is presented.